The Factors Influence on Inflation and Foreign Exchange Reserves of Lao PDR - SELIPHONGXAI, Vaiphoth; HONGSAKHONE, Soulixay; PHOMMANY, Sombath (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research is to study the determinant factors that influence the inflation rate and foreign exchange reserves of Lao PDR; the purpose of the research is 1). Study the factors that affect the inflation rate of the Lao PDR. 2). To study the effect of inflation rate, money supply and economic growth on the foreign exchange reserves of the Lao PDR. The data used is the time series data from 1994-2020 collected from the Bank of Lao PDR to analyze the relationship or effect and implied with OLS robust model. The results indicated that the Kip / Baht exchange rate has the greatest effect on inflation rate with a positive significant. Followed by the unemployment rate, which is negative significant. For the money supply in broad terms has the least effect on inflation and has a positive relationship. Otherwise, it also found that the Kip/USD exchange rate was affected to inflation, but against theoretical, which may cause from the small sample size and the correlation between the Kip/USD and Kip/Baht exchange rates. However, the independent variables used in the model can only explain the inflation rate at 72%. As for the simulation model of the effect of inflation rate, money supply and economic growth on the foreign exchange reserves, it was found that all the variables are statistically significant. The money supply and the economic growth have the positive relationship significance with foreign exchange reserves at a statistical significance level of 0.01, while the inflation rate has a negative relationship with a statistical significance level of 0.05 and the independent variables used in the model can explain the variable up to 83.16%.